The Effect of Resistance Band Training on Topspin Power in Table Tennis - Burhan, Zakir; Hidayat, Dodi firda; Ashari, L. Hasan; Herlina, Herlina (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aimed to determine the effect of resistance band training on increasing top spin power in table tennis among PTM Mantang athletes in 2025. The research method used was a quasi-experimental design with a one-group pretest-posttest. Twenty athletes were sampled using a total sampling technique. The instrument used was a medicine ball throw test from a seated position, modified to resemble a top spin movement. Each athlete was given three attempts during the pretest and posttest, and the highest score was used in the analysis. Normality testing was performed using the Shapiro-Wilk test, and the results showed that the data were normally distributed. Therefore, analysis continued using a paired sample t-test. The test results showed a mean difference of -0.26000 with a t-value of -9.776 and a significance value of p=0.001 (p<0.005). This indicates a significant difference between the pretest and posttest. Thus, resistance band training has been shown to have a significant effect on increasing top spin power in PTM Mantang table tennis athletes.